1998
DOI: 10.1095/biolreprod58.6.1476
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinases Modulate Capacitation of Human Spermatozoa1

Abstract: Recent evidence indicates the presence of p21 Ras and of a protein with characteristics similar to mitogen-activated protein kinases (MAPKs), also known as extracellular signal-regulated kinases (ERKs), in mammalian spermatozoa, suggesting the occurrence of the Ras/ERK cascade in these cells. In the present study we investigated the subcellular localization of ERKs and their biological functions in human spermatozoa. Immunohistochemistry, immunofluorescence, confocal microscopy, and immunoelectron microscopy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 46 publications
5
105
0
1
Order By: Relevance
“…The level at which this suppression occurs is not known, however, it is upstream of ERK 1/2. FGFR-1 in sperm development and function suppressed capacitation and is consistent with previously published data indicating that the MAPK activation is involved in capacitation (Ashizawa et al, 1997;de Lamirande and Gagnon, 2002;Luconi et al, 1998;O'Flaherty et al, 2005). It suggests that FGFR-1/PI3K activation acts either directly or indirectly on MAPK activation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The level at which this suppression occurs is not known, however, it is upstream of ERK 1/2. FGFR-1 in sperm development and function suppressed capacitation and is consistent with previously published data indicating that the MAPK activation is involved in capacitation (Ashizawa et al, 1997;de Lamirande and Gagnon, 2002;Luconi et al, 1998;O'Flaherty et al, 2005). It suggests that FGFR-1/PI3K activation acts either directly or indirectly on MAPK activation.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Fig. 3B, and consistent with previously published data on human sperm (de Lamirande and Gagnon, 2002;Luconi et al, 1998), the MAPK pathway, as indicated by an increase in ERK1/2 phosphorylation, became activated during BWW induced capacitation of wild-type sperm ie. time 0 minutes versus time 90 minutes.…”
Section: Changes In Mapk and Pi3k Signalingsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides the well-characterized protein kinase A (PKA), other Ser/Thr kinases and the ERKs have been involved in sperm capacitation and acrosome reaction (Luconi et al 1998, du Plessis et al 2001, Liguori et al 2005. More recently, specific targets to PKA phosphorylation has been established in human (O'Flaherty et al 2004, Moseley et al 2005) and boar sperm (Harrison 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several signal transduction pathways have been demonstrated to be associated with sperm capacitation, including the extracellular signal-regulated kinase pathway (Luconi et al 1998, de Lamirande & Gagnon 2002, the cyclic AMP/protein kinase A pathway (Visconti et al 1995b, Breitbart 2003, and the reactive oxygen species affected pathway (de Lamirande & O'Flaherty 2008). We can speculate that SPINKL may affect the capacitation-related signal transduction machinery of sperm.…”
Section: Discussionmentioning
confidence: 80%